Prediction of the therapeutic mechanism responsible for the effects of Sophora japonica flower buds on contact dermatitis by network-based pharmacological analysis. (10th May 2021) - Kim, Younsook; Oh, Yoona; Lee, Hongbum; Yang, Beodeul; Choi, Chan-Hun; Jeong, Hyunwoo; Kim, Hyungwoo; An, Wongun
Abstract: Ethnopharmacological relevance: The flower buds of Sophora japonica L. are a major traditional medicine in China, Japan, and Korea and are used to stop bleeding and 'cool the blood'. Accordingly, they are used to treat bleeding haemorrhoids, hypertension, and pyoderma. In addition, it was recently found that the flower buds of S. japonica (SJ) have cosmetic whitening properties. Materials and methods: Compounds in SJ and their targets and related diseases were investigated using the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and analysis platform. Target gene information was obtained from the UniProt database. Network construction was carried out using Cytoscape 3.72. Contact dermatitis (CD)-related gene searching was performed using the Cytoscape string App. Docking analysis was conducted using AutoDock Vina. Six-week-old Balb/c male mice with DNFB (1-fluoro-2, 4-dinitrofluorobenzene)-induced CD were treated with a methanol extract of the flower buds of S. japonica (MESJ), and its effects on skin colour, lesions, and immune cell infiltration, and on histopathological abnormalities such as epidermal hyperplasia were investigated. Results: Eleven compounds targeted 13 CD-related genes, that is, serum albumin (ALB), prostaglandin G/H synthase (COX) 2, C-X-C motif chemokine (CXCL) 2, CXCL10, ICAM1, IFN-γ, IL-10, IL-1α, IL-1β, IL-2, IL-6, E-selectin, and TNF. In the murine DNFB model, MESJ significantly suppressed scaling, erythema, and skin thickening as compared with DNFB controls and epithelial hyperplasia and immune cell infiltrations induced by repeated DNFB application. Conclusions: Our animal study showed that the mode of action of MESJ was closely related to the prevention of epithelial hyperplasia and immune cell infiltration. The results obtained demonstrated that the flower buds of S. japonica offer a potential means of treating CD, and suggest that the therapeutic mechanism of CD is explained by relations between 11 major components of SJ, including kaempferol and quercetin, and 13 CD-related genes. Graphical abstract: Image 1 Highlights: Network-based pharmacological analysis in SJ provides holistic information on compound-target-disease correlations. Eleven compounds in SJ targeted 13 CD-related genes. MESJ alleviated DNFB-induced CD-like skin lesions in mice. MESJ suppressed epithelial hyperplasia and immune cell infiltration into inflamed tissue.